The Prevalence and Prognostic Significance of Polyomavirus Infection in Patients with Urothelial Carcinoma of the Bladder - Wu, Sheng-Wen; Liou, Jia-Hung; Yeh, Kun-Tu; Hung, Tung-Wei; Chang, Horng-Rong (Urology Journal, 2016)
Purpose: Human polyomaviruses (PV) has been associated with oncogenicity; however, the association between human bladder cancer and PV remains inconclusive. Moreover, whether PV has the interaction with p53 in tumorigenesis and their prognostic significance on human bladder cancer has yet to be determined. Materials and Methods: Bladder tumor specimens and clinical parameters from 74 patients with urothelial carcinoma were collected. Immunohistochemical analysis using monoclonal antibodies specific to PV large tumor antigen (TAg) and p53 protein was performed to investigate the involvement of PV in human bladder tumorigenesis and the prognostic significance of TAg and p53 expressions using Cox proportional hazards model. Results: The mean age of the 74 patients at diagnosis was 64 years and 61 (82.4%) were male. The expression of PV TAg protein was found in 45 (60.8%) tumor samples, but was not correlated with the expression of p53 (P = .280). The detection of PV TAg was significantly associated with tumor stage (P = .001) but not decreased overall survival (OS) or cancer-specific survival (CSS) (P = .661 and .738, respectively). However, the p53 overexpression was significantly associated with decreased CSS (P = .028). In multivariate Cox proportional hazards analysis, age and p53 overexpression were predictors of OS (P = .026) independently of tumor stage and CSS (P = .042), respectively. Conclusion: We found that PV, which was detected in a significant percentage of tumor specimens, may be an important co-factor in the tumorigenesis of the bladder in humans. However, only p53 overexpression was associated with predicting CSS independently of tumor stage.